2011
DOI: 10.1155/2011/314952
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Emitting Metal Nanocavity Lasers

Abstract: There has been considerable interest in metallic nanolasers recently and some forms of these devices constructed from semiconductor pillars can be considered as surface-emitting lasers. We compare two different realized versions of these nanopillar devices, one with a trapped cutoff mode in the pillar, another with a mode that propagates along the pillar. For the cutoff mode devices we introduce a method to improve the output beam characteristics and look at some of the challenges in improving such devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recent studies have suggested that the use of metal-clad cavities can be advantageous for on-chip applications due to their ultra-small fingerprint and efficient coupling with integrated waveguides [1,2]. To accomplish high quality factors over 1000, both the metallic absorption and the leakage into the substrate must be effectively suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that the use of metal-clad cavities can be advantageous for on-chip applications due to their ultra-small fingerprint and efficient coupling with integrated waveguides [1,2]. To accomplish high quality factors over 1000, both the metallic absorption and the leakage into the substrate must be effectively suppressed.…”
Section: Introductionmentioning
confidence: 99%